Carbon dioxide capture using gas hydrates technology - Dashti, Hossein (Curtin University, 2019)
Carbon dioxide (CO2) capture has been a significant topic of research and development activities over the past two decades. As a highly potential novel method, hydrate-based CO2 capture (HBCC) has received increasing attention within related industries, due to such advantages as the mild operating pressure and temperature that is required, the ease of regeneration and its unique separation mechanism. This thesis studied the kinetics modeling of gas hydrate formation for CO2 hydrates.